Quantitative kinetic modelling and mapping of cerebral glucose transport and metabolism using glucoCESL MRI. Issue 11 (November 2022) - Dickie, Ben R; Jin, Tao; Wang, Ping; Hinz, Rainer; Harris, William; Boutin, Hervé; Parker, Geoff JM; Parkes, Laura M; Matthews, Julian C
Chemical-exchange spin-lock (CESL) MRI can map regional uptake and utilisation of glucose in the brain at high spatial resolution (i.e sub 0.2 mm 3 voxels). We propose two quantitative kinetic models to describe glucose-induced changes in tissue R 1ρ and apply them to glucoCESL MRI data acquired in tumour-bearing and healthy rats. When assuming glucose transport is saturable, the maximal transport capacity ( T max ) measured in normal tissue was 3.2 ± 0.6 µmol/min/mL, the half saturation constant ( K t ) was 8.8 ± 2.2 mM, the metabolic rate of glucose consumption ( MR glc ) was 0.21 ± 0.13 µmol/min/mL, and the cerebral blood volume ( v b ) was 0.006 ± 0.005 mL/mL. Values in tumour were: T max  = 7.1 ± 2.7 µmol/min/mL, K t  = 14 ± 1.7 mM, MR glc  = 0.22 ± 0.09 µmol/min/mL, v b  = 0.030 ± 0.035 mL/mL. T max and K t were significantly higher in tumour tissue than normal tissue (p = 0.006 and p = 0.011, respectively). When assuming glucose uptake also occurs via free diffusion, the free diffusion rate ( k d ) was 0.061 ± 0.017 mL/min/mL in normal tissue and 0.12 ± 0.042 mL/min/mL in tumour. These parameter estimates agree well with literature values obtained using other approaches (e.g. NMR spectroscopy).